2010
DOI: 10.1097/mnm.0b013e32833767e0
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and 18FDG uptake in atherosclerotic carotid plaques

Abstract: GLUT-1, HK2, CD68, and cathepsin K remained in both multivariate models and thus provided independent information regarding FDG uptake. We suggest that FDG uptake is a composite indicator of macrophage load, overall inflammatory activity and collagenolytic plaque destabilization. Accordingly, FDG-PET could prove to be an important predictor of cerebrovascular events in patients with carotid plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 27 publications
4
76
0
2
Order By: Relevance
“…The largest study to date, that examined over 100 subjects, found that those in the highest quartile of CRP had the greatest degree of vascular FDG uptake, regardless of whether they also had elevated LDL cholesterol or not [67]. Finally, in a study of carotid disease in patients undergoing endarterectomy, gene expression markers of vulnerability GLUT-1, CD68, cathepsin K and HK2 were found to predict the degree of arterial FDG accumulation [68].…”
mentioning
confidence: 98%
“…The largest study to date, that examined over 100 subjects, found that those in the highest quartile of CRP had the greatest degree of vascular FDG uptake, regardless of whether they also had elevated LDL cholesterol or not [67]. Finally, in a study of carotid disease in patients undergoing endarterectomy, gene expression markers of vulnerability GLUT-1, CD68, cathepsin K and HK2 were found to predict the degree of arterial FDG accumulation [68].…”
mentioning
confidence: 98%
“…18 F-FDG signals within atherosclerotic plaques reflect the metabolic activity of macrophages and therefore plaque inflammation. Indeed, in vivo 18 F-FDG uptake is strongly correlated with macrophages density within excised carotid plaques, as well as gene expression associated with vascular inflammation [117,118]. Vascular 18 F-FDG signals have also been shown to be significantly correlated with presence of traditional cardiovascular risk factors (e.g.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…The technique can be modified slightly (by increasing the 18 F-FDG circulation time) for application in arterial disease, such as atherosclerosis (20)(21)(22) and vasculitis (23), as a surrogate marker of inflammation. It is believed that the arterial 18 F-FDG signal reflects glucose accumulation, predominantly by macrophages (24) and other plaque inflammatory cells (25), which can be amplified by hypoxia (26). High levels of 18 F-FDG accumulation in the carotid arteries and aorta are markers of high-risk, unstable disease and may predict future clinical events (27).…”
Section: Role Of Pet Imaging In Aneurysm Diseasementioning
confidence: 99%